United States : 2019 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2019)
The U.S. economy is in the longest expansion in recorded history. Unemployment is at levels not seen since the late 1960s, real wages are rising, and inflationary pressures remain subdued. Economic activity, while still growing above potential, is expected to slow to around 2.6 percent this year and 1.9 percent in 2020.